2018
DOI: 10.1002/ejsp.2548
|View full text |Cite
|
Sign up to set email alerts
|

Right‐ and left‐wing prejudice toward dissimilar groups in cultural and economic domains

Abstract: According to recent studies, people on both the political right and left show prejudice toward groups whose beliefs are in conflict with their own. This prediction applies to both cultural and economic dimensions of political beliefs. In three studies (N = 499) we demonstrate that people on both the cultural and economic right and left show negative attitudes toward groups on the other side of the given spectrum and that underlying this effect is the perception of value violation. In two out of three studies, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…On the social dimension, social conservatism was associated with prejudice towards groups perceived to be socially liberal, whereas social liberalism was associated with prejudice towards groups perceived to be social conservative. On the economic dimension, economic conservatism was associated with prejudice towards groups perceived to be economic liberals, whereas economic liberalism was associated with prejudice towards groups perceived to be economic conservatives (Crawford et al, 2017;Czarnek et al, 2019). These effects were exacerbated when the targets were described as extreme, suggesting the perceived worldview conflict (sometimes measured in these studies as value violations) accounts for the effects (Czarnek et al, 2019).…”
Section: Testing Three Dimension Specific Hypotheses the Three Dimenmentioning
confidence: 81%
See 2 more Smart Citations
“…On the social dimension, social conservatism was associated with prejudice towards groups perceived to be socially liberal, whereas social liberalism was associated with prejudice towards groups perceived to be social conservative. On the economic dimension, economic conservatism was associated with prejudice towards groups perceived to be economic liberals, whereas economic liberalism was associated with prejudice towards groups perceived to be economic conservatives (Crawford et al, 2017;Czarnek et al, 2019). These effects were exacerbated when the targets were described as extreme, suggesting the perceived worldview conflict (sometimes measured in these studies as value violations) accounts for the effects (Czarnek et al, 2019).…”
Section: Testing Three Dimension Specific Hypotheses the Three Dimenmentioning
confidence: 81%
“…hypotheses have now been tested in 10 samples from the United States and Poland using several different measures of prejudice, including feeling thermometers, the implicit association test, and the dictator game (Crawford et al, 2017;Czarnek, Szwed, & Kossowska, 2019). People's positions on social and economic dimensions of political ideology were measured using people's self-identification as liberal or conservative on social and economic dimensions, or with people's support for various social and economic political policies.…”
Section: Testing Three Dimension Specific Hypotheses the Three Dimenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using heterogeneous target groups, we found that the relationship between conservatism and prejudice reversed depending on the perceived ideology of the target group (see Brandt, Reyna, Chambers, Crawford, & Wetherell, 2014, for an initial review). These findings have been extended to different dimensions of political ideology (i.e., social and economic; Crawford et al, 2017; Czarnek, Szwed, & Kossowska, 2018), ideological worldviews (i.e., right-wing authoritarianism and social-dominance orientation; Crawford et al, 2015), and religious fundamentalism (Brandt & Van Tongeren, 2017; Kossowska, Czernatowicz-Kukuczka, & Sekerdej, 2017) and held when using representative target groups (Brandt, 2017). In each case, people on the political left express prejudice toward people perceived to be on the political right, and people on the political right express prejudice toward people perceived to be on the political left.…”
Section: The Findingsmentioning
confidence: 90%
“…The researchers search for the reasons for this incoherence mainly at the macro level, referring to specific socio-historical, cultural or political conditions that may have shaped the attitudes and political orientations of citizens [ 75 ]. For example, as Poland was under communism for many years, maintaining the status quo (traditionally: conservatism/rightism) consists precisely in preserving the situation in which the state looks after the economy and the citizens (i.e., left-wing views) rather than introducing free market principles (right-wing, neoliberal views in the Western sense) [ 76 ]. Some studies have also sought the sources of the incoherence at the micro level.…”
Section: Introductionmentioning
confidence: 99%